Analyzing the Influence of Rural-to-Urban Migration on the Economic Activity and Financial Behavior of Migrant Households in Nepal - Khanal, Rajiv (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates how rural-to-urban migration influences the economic activities and financial behaviour of migrant households in Lumbini Province, Nepal. In many regions of Nepal, people leave rural areas due to poor job prospects, lack of essential services, limited income, inadequate educational facilities, and insufficient cultivable land. These factors drive them towards cities in search of better employment, education, healthcare, and living standards. This research aims to examine how these reasons for migration affect the way families work, earn, spend, and manage money after relocating to urban areas.A mixed-methods research design was employed, combining both quantitative and qualitative data. The study gathered survey data from 404 migrant households using structured questionnaires and conducted in-depth interviews with 33 participants. The analysis utilized Smart PLS for structural equation modelling to examine relationships between migration drivers, economic activity, and financial behavior. Thematic analysis of interview data helped clarify the survey findings.The results show that employment opportunities, lack of basic services, inadequate income sources, education facilities, and scarcity of land have significant effects on both the economic activities and financial behavior of migrant families. Economic activity was found to be a key factor that connects migration drivers with financial behavior. Migrants often shift from farming to non-agricultural jobs, change their savings habits, use digital banking, and join community savings groups after moving to cities.This study highlights that migration is not only a shift in location but also a change in the economic and financial lives of families. The findings suggest that policymakers should design better programs to support migrant families, improve rural services, and manage urban migration. The study contributes new insights into the migration experience in Nepal and offers a basis for further research and planning in similar contexts.